High Expression of Pd-1 in Circulating Cells of Patients With Advanced Colorectal Cancer Receiving Adjuvant Therapy - Bakhrebah, Muhammed A. (Technol Cancer Res Treat, 2020)
Among all cancer types, colorectal cancer is the third most common in men and the second most common in women globally. Generally, the risk of colorectal cancer increases with age, and colorectal cancer is modulated by various genetic alterations. Alterations in the immune response serve a significant role in the development of colorectal cancer. In primary cancer types, immune cells express a variety of inhibitory molecules that dampen the immune response against tumor cells. Additionally, few reports have demonstrated that classical chemotherapy promotes the immunosuppressive microenvironment in both tissues and immune cells. This study assessed the expression levels of genes using RT-qPCR associated with the immune system, including interferon-γ, programmed death-1, β2-microglobulin, human leukocyte antigen-A, CD3e, CD28 and intracellular adhesion molecule 1, in patients with colorectal cancer, as these genes are known to serve important roles in immune regulation during cancer incidence. Gene expression analysis was performed with the whole blood cells of patients with colorectal cancer and healthy volunteers. Compared with the normal controls, programmed death-1was highly expressed in patients with advanced-stage colorectal cancer. Furthermore, the expression of programmed death-1 was higher in patients receiving adjuvant therapy, which suggests the therapy dampened the immune response against tumor cells. The results of the present study indicate that classical adjuvant therapies, which are currently used for patients with colorectal cancer, should be modulated, and a combination of classical therapy with anti-programmed death-1 antibody should be conducted for improved management of patients with colorectal cancer.